FENOMENA DOOR-TO-DOOR DI TENGAH KRISIS SEKOLAH DESA NEBURA - Salmawaty Salmawaty; Sarina Londa Mukin; Maria Yustalia So'i; Maria Novan Novita Laju (Jurnal Manajemen Pendidikan, 2026)
The Education serves as a fundamental pillar of human resource development and plays a strategic role in improving the quality of community life. Schools in rural areas face serious challenges of declining student enrollment driven by socioeconomic constraints, limited access to education, and low parental participation. SD Inpres Nebura, an elementary school in Nebura Village, Sikka Regency, East Nusa Tenggara, is experiencing a critical condition with only around 38 students across six grade levels, threatening the sustainability of the learning process. In response to this crisis, SD Inpres Nebura implemented a door-to-door strategy in which teachers conduct direct home visits to prospective students' families. This study aims to describe the implementation of the door-to-door strategy in student enrollment, identify supporting factors, and describe inhibiting factors in its implementation. This research employed a descriptive qualitative approach. Data were collected through in-depth interviews distributed via Google Form consisting of 30 questions to six parents of prospective students selected through purposive sampling. Data were analyzed using the Miles dan Huberman model through data reduction, data display, and conclusion drawing. Data validity was ensured through source and method triangulation and member checking. The findings reveal that the implementation was carried out through three stages: preparation, direct home visits, and follow-up, with personal communication that built trust.